Pemberdayaan Warga IOM Melalui Urban Farming: Solusi Budidaya Hidroponik dan Jamur di Daerah Pengungsian Sawotratap, Sidoarjo - Adreansyah Putra, Mochammad Kharis; Seftia Aulia Putri; Diva Raissa Anindya; Rhenald Thio Arifin; Mita Rahmawati; Ricky Alejandro Martin (Yayasan Cendekia Gagayunan Indonesia, 2025)
Community Service (KKN) is a form of student service to the community that implements the Tri Dharma of Higher Education. This program aims to apply students' knowledge and skills in solving real problems in society. Based on an initial survey in Sawotratap Village, Gedangan District, Sidoarjo Regency, the KKN team identified modern agriculture and utilized the potential of limited land and increased food independence. One of the innovations developed is Hydroponics and Mushrooms. In the installation of making simple hydroponics as an alternative to modern agriculture, by planting several types of plants such as kale, spinach, lettuce, red spinach. The main goal is to provide solutions for residents in utilizing limited land and increasing food independence. The implementation stages begin with socialization and education to residents regarding the benefits of hydroponics, the tools and materials needed, and the steps to make it. After that, the hydroponic installation is assembled using simple language such as PVC pipes, RockWool, and plant seeds.